EVALUASI ATAS LAPORAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH BERBASIS HASIL - Firman Rahmadoni; Erwandi Erwandi (JEM Jurnal Ekonomi dan Manajemen, 2018)
This study aims to analyze and evaluate the process flow logic that guided the preparation of performance reports to Minister of PAN and RB No. 29 of 2010, difficulties in the preparation of performance reports and key performance indicators are result oriented. The method used in this study is using a qualitative method. Sampling This study used purposive sampling to select respondents who are expert officials who are involved and there is a direct relationship in the process of preparing performance reports Pangkalpinang. Methods of data collection, in addition, to studying the document using semi-structured interviews and questionnaires. Performance evaluation and analysis using Blueprint with Friedman's Four quadrant approach. Based on the analysis of four quadrant attribute that most of the key performance indicators in government performance reports document attachments Pangkalpinang still a quantity of 59% means the efforts undertaken new activities is the quantity of effort but has not been followed by the quality of the efforts of only 3%. While the performance indicators that describe the result by 38%. So the outcome performance indicators Government Pangkalpinang largely not based measure outcomes or benefits that can be felt by the public/customers